ANALISIS POLIFENOL EKSTRAK TEH TUBRUK KEMASAN MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Hadi Barru Hakam Fajar Siddiq, Rizka Del Rizka Della Yunita Dewi, Jati Riyuwani (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2016)
The purpose of this research is determine the polyphenol content of brewed tea. Sample were used three sample. Polyphenol compounds of packaged tea were extracted using percolation method with ethanol 70%. Qualitative test were used using FeCl3 reagent and quantitative test polyphenol content were determined using UV-Vis spectrophotometry method with Folin Ciocalteau reagent. Galic acid was used as comparator in this research. The result of qualitative test is all sample of packaged tea containing polyphenol. Polyphenol content sample A, B, and C, with peercolation method were respectively 0,538; 0,554; and 0,470; %b/b.Keyword: packaged tea, polyphenol, percolation, UV-Vis spectrophotometry